1997
DOI: 10.1002/(sici)1096-8628(19971031)72:3<286::aid-ajmg6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen storage disease type 1a in Israel: Biochemical, clinical, and mutational studies

Abstract: Glycogen storage disease type 1a (von Gierke disease, GSD 1a) is caused by the deficiency of microsomal glucose-6-phosphatase (G6Pase) activity which catalyzes the final common step of glycogenolysis and gluconeogenesis. The recent cloning of the G6Pase cDNA and characterization of the human G6Pase gene enabled the characterization of the mutations causing GSD 1a. This, in turn, allows the introduction of a noninvasive DNA-based diagnosis that provides reliable carrier testing and prenatal diagnosis. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Asn 203 is located in a cytoplasmic loop and mutation (N203A) of this residue had no adverse effects on protein synthesis, as similar amount of G6Pase were synthesized by WT or the N203A construct. Moreover, the N203A mutant retained 37% of WT activity, whereas all mutations uncovered in the G6Pase gene of GSD-1a patients abolish or markedly reduce (retaining 18% or less of WT activity) G6Pase activity (7,14,15,23,24). This suggests that the structural requirement of the cytoplasmic loops is less stringent than other features of human G6Pase.…”
Section: Characterization Of G6pase Mutants Lacking One or More Glycomentioning
confidence: 95%
See 1 more Smart Citation
“…Asn 203 is located in a cytoplasmic loop and mutation (N203A) of this residue had no adverse effects on protein synthesis, as similar amount of G6Pase were synthesized by WT or the N203A construct. Moreover, the N203A mutant retained 37% of WT activity, whereas all mutations uncovered in the G6Pase gene of GSD-1a patients abolish or markedly reduce (retaining 18% or less of WT activity) G6Pase activity (7,14,15,23,24). This suggests that the structural requirement of the cytoplasmic loops is less stringent than other features of human G6Pase.…”
Section: Characterization Of G6pase Mutants Lacking One or More Glycomentioning
confidence: 95%
“…1). Twelve missense mutations and the codon deletion mutation (⌬F327) were further examined for G6Pase activity in transient expression assays (7,14,15,23,24). These include R83C and R83H, which altered Arg…”
Section: Characterization Of G6pase Mutants Lacking One or More Glycomentioning
confidence: 99%
“…However, by contrast, some mutations may be predominant in particular populations: the 727 G>T mutation accounts for 88% of mutant allles in Japaneses patients (Kajihara et al, 1995), the R83C mutation accounts for 93% of mutant alleles in Jewish patients (Parvari et al, 1997). Thus, for a patient with GSD Ia, it is important, prior to molecular investigations to have a precise knowledge of geographical origins of both parents.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to GSD Ia, most studies identified mutations on all alleles investigated [1,3,11,14,17,38,42,50,62]. In a few publications, however, mutations were not iden- Only found in a patient homozygous for M5R and heterozygous for R83C, the latter not being included in this table [54] c New mutations S13 tified on several alleles with the poorest mutation detection rate of only 75% reported by Hu¨ner et al [11].…”
Section: Glycogen Storage Disease Type Iamentioning
confidence: 99%
“…In one of our laboratories, mutations were identified on all 98 G6PC alleles analyzed to date [48]. GSD Ia is a genetically heterogenous disorder with 76 different mutations detected so far among mostly compound heterozygous patients from a total of 424 different families combining our own and published data (Table 1) [1,3,8,11,14,15,16,17,19,23,24,26,33,35,38,39,41,42,45,48,50,51,53,61,62,63,64]. Taking all these patients together, there are no true common mutations and more than 50% appear to be private mutations.…”
Section: Glycogen Storage Disease Type Iamentioning
confidence: 99%